Zingiber officinale (Ginger) as a treatment for inflammatory bowel disease: A review of current literature - Sadeghi Poor Ranjbar, Fatemeh; Mohammadyari, Fatemeh; Omidvar, Atharzahra; Nikzad, Farhad; Doozandeh Nargesi, Nooria; Varmazyar, Majid; Dehghankar, Soroush; Vosoughian, Fatemeh; Olangian-Tehrani, Sepehr; Nanbakhsh, Sepehr; Mansourian, Tina; Deravi, Niloofar; et al. (Frontiers in Drug Discovery, 2022)
Inflammatory bowel disease (IBD) is a term used for a variety of conditions involving persistent inflammation of the digestive system. Ulcerative colitis (UC) and Crohn’s disease (CD) are examples of IBD. There were some treatments like Amino salicylates, glucocorticoids, immunosuppressants, antibiotics, and surgery which have been used for treating IBD. However, the short and long-term disabling adverse effects, like nausea, pancreatitis, elevated liver enzymes, allergic reactions, and other life-threatening complications remain a significant clinical problem. On the other hand, herbal medicine, believed to be safer, cheaper, and easily available, has gained popularity for treating IBD. Nowadays, Ginger, the Rizhome of Z. officinale from the Zingiberaceae family, one of the most commonly used fresh spices and herbs, has been proposed as a potential option for IBD treatment. According to upper issues, IBD treatment has become one of the society’s concerns. So, this review aims to summarize the data on the yin and yang of ginger use in IBD treatment.